New observation of severe tooth malformation in a female patient with ectodermal dysplasia due to the EDA splice acceptor variant c.742-2A & gt;G - Reinhold Vivian; Syrjänen Stina; Kankuri-Tammilehto Minna (WILEY, 2025)
Background: Ectodermal dysplasias are inherited disorders, which are characterized by congenital defects in two or more ectodermal structures such as skin, sweat glands, hair, nails, teeth, and mucous membranes.
Method: Here, we describe a new observation of significant oligodontia in a female patient with the EDA gene variant c.742-2A>G.
Results: The results strongly suggest that the EDA gene variant c.742-2A>G is pathogenic. The oligodontia in the proband was exceptionally severe.
Conclusion: We demonstrate that the very rare splice acceptor variant EDA c.742-2A>G is associated with severe oligodontia even in females. Our study points that this variant is pathogenic. An early identification of this variant is crucial for planning adequate treatment and follow-up in time by a multidisciplinary team.